Sanguisorba officinalis L. ethanolic extracts and essential oil – chemical composition, antioxidant potential, antibacterial activity, and ex vivo skin permeation study - Muzykiewicz-Szymańska, Anna; Nowak, Anna; Kucharska, Edyta; Cybulska, Krystyna; Klimowicz, Adam; Kucharski, Łukasz (Frontiers in Pharmacology, 2024)
Introduction Sanguisorba officinalis L. is classified as a medicinal plant and used in traditional medicine. The root of this plant is mainly used as a medicinal raw material, but the above-ground parts are also a valuable source of health-promoting biologically active compounds. Method The study aimed to evaluate the antioxidant activity and total polyphenol content (TPC) of extracts prepared in 70% and 40% aqueous ethanol solution (dry extract content 50–500 g/L) from the aerial parts of S. officinalis. The essential oil was isolated from the tested raw material, and its composition was determined using GC-MS. Ethanolic extracts and essential oil have been tested for antibacterial activity. The extract in 70% v/v ethanol (dry extract content: 500 g/L) was subjected to HPLC analysis for the content of selected phenolic acids and an ex vivo skin permeation study. The ability of these metabolites to permeate and accumulate in the skin was analysed. Results Extracts prepared at both ethanol concentrations showed similar antioxidant activity and TPC. Depending on the method, concentration of solvent, and dry extract content (50–500 g/L), the activity ranged from 1.97 to 84.54 g Trolox/L. TPC range of 3.80–37.04 g GA/L. Gallic acid (424 mg/L) and vanillic acid (270 mg/L) had the highest concentrations among the phenolic acids analysed. Vanillic acid (10 μg) permeates the skin at the highest concentration. The highest accumulation in the skin was found for 2,5-dihydroxybenzoic acid (53 μg/g skin), 2,3-dihydroxybenzoic acid (45 μg/g skin), and gallic acid (45 μg/g skin). The tested ethanolic extracts exhibited antibacterial activity. Samples with a dry extract concentration of 500 g/L showed the largest growth inhibition zones. The most sensitive strains to these extracts were P. aeruginosa (24 mm), S. lutea (23 mm), and S. pneumoniae (22 mm). The smallest inhibition zones were observed for B. subtilis (17 mm). The essential oil showed weaker antimicrobial activity (growth inhibition zone 8–10 mm). The GC-MS method identified 22 major components of the essential oil, including aliphatic hydrocarbons, unsaturated terpene alcohols, aliphatic aldehydes, unsaturated and saturated fatty acids, sesquiterpene, phytyl ester of linoleic acid, nitrogen compound, phytosterol, terpene ketone, phenylpropanoids, aliphatic alcohol, diterpenoid, aromatic aldehyde, and aliphatic carboxylic acid. Discussion The conducted research has shown that ethanolic extracts from Sanguisorbae herba are a valuable source of compounds with antibacterial and antioxidant potential, including phenolic acids. The fact that selected phenolic acids contained in the tested extract have the ability to permeate and accumulate in the skin provides the basis for conducting extended research on the use of extracts from this plant raw material in cosmetic and pharmaceutical preparations applied to the skin.